Development of Novel Primers and Probes Based on its 2 Region Using Nested-PCR and DNA Hybridization Array for Candida Species Identification - Chieng, David Ching Soo (2007)
Sensitivity, specificity, simplicity, speed, and economy fairly well describe the desirable attributes of any clinical diagnostic test. In the mycology laboratory, the detection and differentiation of Candida species usually rely on the morphological, physiological, and biochemical characteristics which are complex, frequently slow to appear, sometimes vary within a species, and usually require significant experience to evaluate. In this study, novel primers and probes had been developed for the identification of 8 Candida species using nested-PCR and DNA hybridization array by focusing on a single parameter. This parameter is the identification of nucleotide sequence from ITS 2 region that is known to be unique for the Candida species. These distinctive sequences were used to design and develop Candida species-specific primers and probes for nested-PCR and DNA hybridization array, respectively. For nested-PCR, the universal fungal primers, ITS 3 and ITS 4 were used to amplify the portion of the 5.8S and 28S rDNA, and the ITS 2 region of Candida species. The amplicons were used as template together with developed species-specific primers in the subsequent amplification. The results were analyzed using agarose gel electrophoresis. In addition, species-specific probes were used to hybridize to the biotinylated Candida species ITS 2 amplicons via DNA hybridization array. The amplicons were detected colorimetrically in strip format. The sensitivity and specificity of the Candida species-specific primers and probes were evaluated. The 8 Candida ATCC strains and 24 clinical isolates did not exhibit cross-priming and cross-hybridization with the species-specific primers and probes in both assays and all the Candida species were correctly identified. In simulated clinical specimens, the sensitivity of the nested-PCR for Candida species detection was 10 cells/mL. However, the detection limit for both PCR using species-specific primers and DNA hybridization array using species-specific probes for the detection of Candida culture DNA was 1-10 cells/mL. Additionally, a preliminary study was done for the screening of 40 healthy donors’ sera using the real-time PCR for the detection of Candida albicans using species-specific primers, CAL1 and CAL3. The melting curve was used for the analyses of the results. 3 out of 40 samples were found to be positive for Candida albicans. It is suggested that the real-time PCR may not be able to distinguish the individuals who are colonized from those who are infected. In conclusion, the nested-PCR and DNA hybridization array using the developed species-specific primers and probes, respectively, in this study are robust, sensitive and can be easily integrated into a clinical diagnostic laboratory with the potential for same-day diagnosis of Candida infection. In addition, the simultaneous differentiation of Candida species via DNA hybridization array allows faster and simpler diagnosis compare to nested-PCR. For real-time PCR screening of the healthy donors’ sera, further evaluation needs to be done to determine a threshold as standard guideline to detect the infectious and colonized Candida albicans and non-albicans Candida species.